High-Throughput Genotyping of Common Chromosomal Inversions in the Afrotropical Malaria Mosquito Anopheles Funestus - Martin Lukindu; R. Rebecca Love; Moussa W. Guelbeogo; Scott T. Small; Melissa T. Stephens; Nathan R. Campbell; N’Fale Sagnon; Carlo Costantini; Nora J. Besansky (Insects, 2020)
Polymorphic chromosomal inversions have been implicated in local adaptation. In anopheline mosquitoes, inversions also contribute to epidemiologically relevant phenotypes such as resting behavior. Progress in understanding these phenotypes and their mechanistic basis has been hindered because the only available method for inversion genotyping relies on traditional cytogenetic karyotyping, a rate-limiting and technically difficult approach that is possible only for the fraction of the adult female population at the correct gonotrophic stage. Here, we focus on an understudied malaria vector of major importance in sub-Saharan Africa, Anopheles funestus. We ascertain and validate tag single nucleotide polymorphisms (SNPs) using high throughput molecular assays that allow rapid inversion genotyping of the three most common An. funestus inversions at scale, overcoming the cytogenetic karyotyping barrier. These same inversions are the only available markers for distinguishing two An. funestus ecotypes that differ in indoor resting behavior, Folonzo and Kiribina. Our new inversion genotyping tools will facilitate studies of ecotypic differentiation in An. funestus and provide a means to improve our understanding of the roles of Folonzo and Kiribina in malaria transmission.